2017
DOI: 10.3390/insects8040111
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Competition between Aedes aegypti and Culex quinquefasciatus (Diptera: Culicidae) Coexisting in Breeding Sites

Abstract: Aedes aegypti and Culex quinquefasciatus are mosquito vectors for several tropical diseases that represent a current public health problem. The ecological requirements for each species are different, however, both species show high biological adaptability, which promotes their coexistence in the same breeding sites. The purpose of this study was to assess the effect of larval association between Ae. aegypti and Cx. quinquefasciatus under different laboratory conditions of food supply and temperature, and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Other investigators have observed that A . aegypti larvae are not always food limited in their normal environment [ 4 , 7 , 10 , 193 , 194 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have observed that A . aegypti larvae are not always food limited in their normal environment [ 4 , 7 , 10 , 193 , 194 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti mortality. Santana-Martínez et al (2017), showed that Ae. aegypti is a superior resource competitor and appears to be capable of competitively affecting Cx.…”
Section: Discussionmentioning
confidence: 99%
“…pipiens s.l . in coexistence with Aedes aegypti L. under laboratory conditions (Santana‐Martínez et al ., ). Whether Cx.…”
Section: Discussionmentioning
confidence: 97%